Chronic Administration of Oil Palm (Elaeis guineensis ) Leaves Extract Attenuates Hyperglycaemic-Induced Oxidative Stress and Improves Renal Histopathology and Function in Experimental Diabetes - Rajavel, Varatharajan; Abdul Sattar, Munavvar Zubaid; Abdulla, Mahmood Ameen; M. Kassim, Normadiah; Abdullah, Nor Azizan (Hindawi Publishing Corporation, 2012)
Oil palm (Elaeis guineensis) leaves extract (OPLE) has antioxidant properties and because oxidative stress contributes to the pathogenesis of diabetic nephropathy (DN), we tested the hypothesis that OPLE prevents diabetes renal oxidative stress, attenuating injury. Sprague-Dawley rats received OPLE (200 and 500 mg kg−1) for 4 and 12 weeks after diabetes induction (streptozotocin 60mg kg−1). Blood glucose level, body and kidney weights, urine flow rate (UFR), glomerular filtration rate (GFR), and proteinuria were assessed. Oxidative stress variables such as 8-hydroxy-2-deoxyguanosine (8-OHdG), glutathione (GSH), and lipid peroxides (LPO) were quantified. Renalmorphology was analysed, and plasma transforming growth factor-beta1 (TGF-β1) was measured. Diabetic rats demonstrated increase in blood glucose and decreased body and increased kidney weights. Renal dysfunction (proteinuria, elevations in UFR and GFR) was observed in association with increases in LPO, 8-OHdG, and TGF-β1 and a decrease in GSH. Histological evaluation of diabetic kidney demonstrated glomerulosclerosis and tubulointerstitial fibrosis. OPLE attenuated renal dysfunction, improved oxidative stress markers, and reduced renal pathology in diabetic animals. These results suggest OPLE improves renal dysfunction and pathology in diabetes by reducing oxidative stress; furthermore, the protective effect of OPLE against renal damage in diabetes depends on the dose of OPLE as well as progression of DN.